Computational fluid dynamics study of tracer gas dispersion in a mine after different ventilation damage scenarios - Xu, Guang; Jong, E.; Luxbacher, K.; Ragab, S. (2012)
Tracer gases are an effective method for assessment of mine ventilation systems, but their dispersion characteristics can differ substantially as ventilation parameters, such as flow path and velocity, vary. This research utilizes Computational Fluid Dynamics (CFD) to model a simplified full scale model mine, details a sensitivity study examining mesh size for an underground coal mine simulation, and examines gas dispersion parameters to determine the optimal model methods for simulation of tracer gases in underground coal mines. These models can be used to determine how a given tracer gas profile might be generated in a mine or areas of a mine that are not accessible, for example, immediately following a mine disaster. Accurate simulation scenarios can allow for the remote determination of the status of the ventilation network, but the sensitivity of the simulation at mine scale must be carefully examined. Copyright © 2012 by SME.